Effects of a natural toxin on life history and gene expression of Eisenia andrei. (2nd January 2014) - van Ommen Kloeke, A.E. Elaine; Gong, Ping; Ellers, Jacintha; Roelofs, Dick
Abstract Earthworms perform key functions for a healthy soil ecosystem, such as bioturbation. The soil ecosystem can be challenged by natural toxins such as isothiocyanates (ITCs), produced by many commercial crops. Therefore, the effects of 2‐phenylethyl ITC were investigated on the earthworm Eisenia andrei using an ecotoxicogenomics approach. Exposure to 2‐phenylethyl ITC reduced both survival and reproduction of E. andrei in a dose‐dependent manner (median effective concentration [EC50] = 556 nmol/g). Cross‐species comparative genomic hybridization validated the applicability of an existing 4 × 44 000 Eisenia fetida microarray to E. andrei. Gene expression profiles revealed the importance of metallothionein (MT) as an early warning signal when E. andrei was exposed to low concentrations of 2‐phenylethyl ITC. Alignment of these MT genes with the MT‐2 gene of Lumbricus rubellus showed that at least 2 MT gene clusters are present in the Eisenia sp. genome. At high‐exposure concentrations, gene expression was mainly affected by inhibiting chitinase activity, inducing an oxidative stress response, and stimulating energy metabolism. Furthermore, analysis by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway implied that the high concentration may have caused impaired light sensitivity, angiogenesis, olfactory perception, learning, and memory. Increased levels of ITCs may be found in the field in the near future. The results presented call for a careful investigation to quantify the risk of such compounds before allowing them to enter the soil on a large scale. Environ Toxicol Chem 2014;33:412–420. © 2013 SETAC